The Benefits Of Integrated Decisions Over Sulphur Content Along The Process Chain: Production Of Pig Iron And Steel - Emmanuel Marchal; G. Martino; F. Silva (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The definition of the chemical specification at multiple steps of the steelmaking process is very common in the industry. Among all elements and compounds, the Sulphur content has a special control over several stages, from the coal blend to the final products. Coke, iron and steelmaking specialists usually agree on a static specification for each intermediate product according to their local operation capacity and production cost. However, local decisions have major impacts on the whole production chain and many global factors should be considered in order to make the best decision. In this study, we will exemplify focusing on Sulphur content concepts and techniques that could be applied to many decisions in an integrated carbon steel plant. The variation of coal and coke prices, the desulphurization cost and time, the processes operating points, the hot metal rate at converters, prices and demands of low and ultra-low Sulphur steel grades are some of the integrated factors that are usually disregarded during the specification process. Mathematical modeling presents itself as a proper option into dealing with all the complexity that emerges from integrating all these processes' trade-offs and decisions. This study presents the results of a mathematical model that encompasses economic, thermal, chemical, and mass balances, physical quality of materials and productivity constraints of all processes of a hypothetical integrated carbon steel plant. It optimizes the iron and steelmaking process on a global and unique objective, dynamically defining targets for product quality to achieve the lowest steel production cost. This study details multiple market-plant scenarios in order to compare economic and operating results of a static vs dynamic specification practice.